Body surface posture evaluation: construction, validation and protocol of the SPGAP system (Posture evaluation rotating platform system). Issue 1 (December 2016) - Schwertner, Debora; Oliveira, Raul; Mazo, Giovana; Gioda, Fabiane; Kelber, Christian; Swarowsky, Alessandra
Abstract Background Several posture evaluation devices have been used to detect deviations of the vertebral column. However it has been observed that the instruments present measurement errors related to the equipment, environment or measurement protocol. This study aimed to build, validate, analyze the reliability and describe a measurement protocol for the use of the Posture Evaluation Rotating Platform System (SPGAP, Brazilian abbreviation). Methods The posture evaluation system comprises a Posture Evaluation Rotating Platform, video camera, calibration support and measurement software. Two pilot studies were carried out with 102 elderly individuals (average age 69 years old, SD = ±7.3) to establish a protocol for SPGAP, controlling the measurement errors related to the environment, equipment and the person under evaluation. Content validation was completed with input from judges with expertise in posture measurement. The variation coefficient method was used to validate the measurement by the instrument of an object with known dimensions. Finally, reliability was established using repeated measurements of the known object. Results Expert content judges gave the system excellent ratings for content validity (mean 9.4 out of 10; SD 1.13). The measurement of an object with known dimensions indicated excellent validity (all measurement errors <1 %) and test-retest reliability. A total of 26 images were needed to stabilize the system. Participants in the pilot studies indicated that they felt comfortable throughout the assessment. The use of only one image can offer measurements that underestimate or overestimate the reality. To verify the images of objects with known dimensions the values for the width and height were, respectively, CV 0.88 (width) and 2.33 (height), SD 0.22 (width) and 0.35 (height), minimum and maximum values 24.83–25.2 (width) and 14.56 – 15.75 (height). In the analysis of different images (similar) of an individual, greater discrepancies were observed in the values found. The cervical index, for example, presented minimum and maximum values of 15.38 and 37.5, a coefficient of variation of 0.29 and a standard deviation of 6.78. Conclusions The SPGAP was shown to be a valid and reliable instrument for the quantitative analysis of body posture with applicability and clinical use, since it managed to reduce several measurement errors, amongst which parallax distortion.